Cutaneous Langerhans cell histiocytosis with subsequent development of haematological malignacies - Wollina, Uwe (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Adult cutaneous Langerhans cell histiocytosis (LCH) is a rare disease. We report two cases illustrating the variability of the clinical presentation andthe response to treatment. In both cases a remission was achieved: in one case a partial remission with psoralen plus UVA irradiation (PUVA) and methotrexate plus topical corticosteroid ointment; in the other case by treatment with thalidomide. Despite a therapeutic response, both patients later developed haematological malignancies: a chronic myelo-monocytic leukaemia and an acute lymphatic leukaemia. In conclusion, patients with adultcutaneous LCH should be monitored carefully so that a secondary malignancy is not overlooked.
Keywords: dermatologija; Histiocitoza Langerhansovih celic; Histiocytosis, Langerhans-Cell; kožne bolezni; Kožne manifestacije; Pathology; Skin Manifestations; Therapy